Talend Open Studio Cookbook - Barton, Rick (Packt Publishing, Limited, 2013)
Primarily designed as a reference book, simple and effective exercises based upon genuine real-world tasks enable the developer to reduce the time to deliver the results. Presentation of the activities in a recipe format will enable the readers to grasp even the complex concepts with consummate ease.Talend Open Studio Cookbook is principally aimed at relative beginners and intermediate Talend Developers who have used the product to perform some simple integration tasks, possibly via a training course or beginner's tutorials.